Women’s Songs: a Look at the Gender Dimension of Lyrical Poems (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The article demonstrates the ways in which one could link the term coined by Vuk Karadžić, women’s songs, with contemporary ideas about gender. The conditioning of oral text by its context makes relative the male/female opposition in the meaning of culture/nature, public/private, mind/body. Due to the fact that some folkloric genres are predominantly created and spread by women, as well as the fact that scientists on the field may find it hard to write down male texts, the gender aspect of the oral production process and the study of oral culture proves to be of utmost importance. The heterogenic corpus of oral lyrical poems forms different cultural models and confirms cultural hierarchy, since the women and girls acquire different attributes – they can be obedient and submissive, but also insubordinate and powerful. Special is paid to the indirect determining of the religious sphere as pertaining to women made by Karadžić, where the ceremonial context, depending on the perspective, can be subversive or affirm the current order. The masks, which accompany the ceremonial poems and practices, prove to be especially significant when considering gender identities, since they are used to make them relative.
Keywords: oral poems; gender; identity; ritual; ritual inversion; context; cultural model